Plasticity of zirconium hydrides: a coupled edge and screw discrete dislocation model. (February 2021) - Reali, Luca; Wenman, Mark R.; Sutton, Adrian P.; Balint, Daniel S.
Abstract: Understanding the plastic behaviour of thin zirconium hydrides is important for its implications on crack nucleation in the Zirconium alloy cladding used in fission reactors. Microvoids originate at fractured hydrides, and their coalescence may lead to the failure of the component. In this work, an innovative discrete dislocation framework is presented together with the preliminary results. The aim is to develop a model that is significantly faster than existing 3D formulations, to make it possible to run a statistical analysis on a simulated microstructure. This comes with limitations, which are discussed together with the planned developments. The model combines two planar and orthogonal simulations. In one only edge, in the other only screw dislocations are allowed, thereby describing all sides of a dislocation loop approximated as a rectangle. The two families of dislocations interact via their elastic stress, and this coupling proved to be important and significantly enhanced the dislocation density. The proposed model enables us to implement a 3D stress analysis of the hydrides. The simulations show that the most critical scenario is when neighbouring slip planes become populated with opposite-signed dislocations. This was observed both in the edge and in the screw case, and was reflected in the principal stress calculated by combining the two. It was also observed that the degree of permeability of the interface to dislocation crossing is inversely correlated to the stress inside the hydride and to the dislocation source activation.